PENGARUH BLENDED LEARNING MENGGUNAKAN MODEL FLIPPED CLASSROOM TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA PADA MATERI PERTIDAKSAMAAN NILAI MUTLAK LINEAR SATU VARIABEL - Tiur Yohana Tampubolon; Lois Oinike Tambunan; Yoel Octobe Purba (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research uses a quantitative research that aims to determine whether there is an effect of Blended Learning using Flipped Classroom model on students’ mathematical reasoning abilities on the linear absolute value inequality of one variable. The type of research used is experimental research in a  quasi experimental from with a nonequivalent control group design. The population of this research were all tenth graders of SMA Negeri 4 Pematangsiantar for the academic year 2022/2023 as many as 357 students. Sampling using purposive sampling technique, while the samples from this research were taken X-PMIA 5 as the experimental class and X-PMIA 6 as control class. The instrumen used is a test of students’ mathematical reasoning abilities in the form of description of 5 equestions. The data analysis technique used to see the effect is using an Z-test, after calculating, obtained Z_hit=2,884 dwith a significant level of 0,05 then obtained Z_tab=1,64. Thus its is known that  〖Z_hit>Z〗_tab is 2,884>1,64 so can be concluded that there is an effect of Blended Learning using Flipped Classroom model on students’ mathematical reasoning abilities on the linear absolute value inequality  one  of variable.